2020
DOI: 10.1016/s2213-8587(20)30271-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for COVID-19-related mortality in people with type 1 and type 2 diabetes in England: a population-based cohort study

Abstract: Background Diabetes has been associated with increased COVID-19-related mortality, but the association between modifiable risk factors, including hyperglycaemia and obesity, and COVID-19-related mortality among people with diabetes is unclear. We assessed associations between risk factors and COVID-19-related mortality in people with type 1 and type 2 diabetes. Methods We did a population-based cohort study of people with diagnosed diabetes who were registered with a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

56
809
12
42

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 801 publications
(972 citation statements)
references
References 21 publications
56
809
12
42
Order By: Relevance
“…In addition to the humoral response data, our cohort also provided additional insights into the relationship between diabetes, hyperglycaemia and COVID-19 pneumonia. First, we confirmed that hyperglycaemia was independently associated with a poorer in-hospital outcome, even after the results were adjusted for age, sex, obesity and other relevant comorbidities, as recently reported [37]. Second, patients with a diagnosis of diabetes, either comorbid or newly diagnosed, with better controlled blood glucose levels had less severe COVID-19 pneumonia and lower mortality risk compared with those with poorly controlled blood glucose during hospitalisation [38].…”
Section: Discussionsupporting
confidence: 86%
“…In addition to the humoral response data, our cohort also provided additional insights into the relationship between diabetes, hyperglycaemia and COVID-19 pneumonia. First, we confirmed that hyperglycaemia was independently associated with a poorer in-hospital outcome, even after the results were adjusted for age, sex, obesity and other relevant comorbidities, as recently reported [37]. Second, patients with a diagnosis of diabetes, either comorbid or newly diagnosed, with better controlled blood glucose levels had less severe COVID-19 pneumonia and lower mortality risk compared with those with poorly controlled blood glucose during hospitalisation [38].…”
Section: Discussionsupporting
confidence: 86%
“…El RR en personas con DM2 y HbA1c menor a 6.5% es más bajo, con sólo un RR de 1.1 (IC95% 1.04-1.18) (B2b). 23 El control de la DM es esencial en los pacientes con Covid-19 (5D). 24 Hay evidencia estadísticamente significativa de que los valores de hemoglobina glucosilada del grupo de 8.1% (IC95%, 7.2-10.1) predicen pronóstico desfavorable, por lo que se tomó el valor de 8% para el criterio de vulnerabilidad.…”
Section: Diabetes Mellitusunclassified
“…36 No se encontraron estudios previos que relacionaran sólo la tasa de filtración glomerular (TFG) previa a salud pública de méxico Hernández-Ávila M y col. la infección con el pronóstico; no obstante, en un estudio que buscó mortalidad en pacientes con DM tipo 2 se hizo un análisis de la TFG previa y se encontró que aquéllos con 30-44 ml/min/1.72m 2 tenían el doble de riesgo que aquéllos con >60 (RR 2.16, IC95% 1.59-2.93), y el riesgo aumentaba aún más cuando la TFG estaba por debajo de 15 (RR 6.8, IC95% 4.65-10.09) (B2b). 23 En una cohorte retrospectiva nacional en China se identificó que la ERC se asoció con mayor riesgo de neumonía por cualquier agente (RR 1.97, IC95% 1.89-2.05; p<0,001) (B2b). 37 Las tasas de neumonía en pacientes con ERC con TFG <30 son casi tres veces mayores (D5).…”
Section: Enfermedad Renal Crónicaunclassified
“…Several initiatives are building COVID- 19 registries or consortia to analyze electronic health record (EHR) data (6,7,9). The expectation is that these resources will provide researchers and clinicians access to a rich source of observational data to understand the clinical progression of COVID-19, to estimate the impact of therapies, and to make predictions regarding outcomes.…”
mentioning
confidence: 99%
“…2) indicate that age is a major risk factor, but ethnicity and gender are also significant when considered univariately. There is great interest and growing peer-reviewed literature on risk factors for COVID-19 mortality: the agility of our approach allows us to quickly re-run queries and rebuild models as new predictors become relevant and the understanding of the disease evolves (17)(18)(19)(20).…”
mentioning
confidence: 99%